(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article discusses the issues of creating new technologies for controlling processes in the near-wellbore zone and methods for the effectiveness of the influence of the electric field on the oil recovery process. The possibility of electroosmotic influence on the displacement of oil by water has also been shown.